Ligand-promoted cobalt-catalyzed radical hydroamination of alkenes - Xuzhong Shen (Nature Portfolio, 2020)
Asymmetric intermolecular hydroamination of alkenes is a challenging process, potentially leading to useful chiral amines. Here, the authors report unsymmetric NNN tridentate ligands promoting the cobalt-catalyzed radical hydroamination of alkenes via hydrogen atom transfer, also in an asymmetric fashion.